Classifying the Fault Type in Underground Distribution System Based on Fuzzy Logic Algorithm - M. Sudha (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper exhibits the best possible information example of fluffy rationale calculation for blame sort characterization in underground link. The proposed calculation utilizing mix of discrete wavelet changes (DWT) and fluffy rationale. The DWT is connected to concentrate high recurrence segment from blame current waveform utilizing mother wavelet daubechies4 (db4). The most extreme coefficients detail of DWT and greatest proportion of DWT, acquired from stage A, B, C and zero succession of blame current waveforms have been utilized as an info factors for choice calculation. The acquired outcomes in term of normal exactness have demonstrated that the most extreme proportion of DWT can accomplished tasteful precision in blame sort order.